Women entrepreneurs in Egypt: A qualitative study of perceptions and challenges - Abdelrhman, Rwan Zakria (AUC Knowledge Fountain, 2019)
Although all entrepreneurs and business owners encounter obstacles and barriers, the challenges that female entrepreneurs face in Egypt are surmount. Female entrepreneurs in Egypt lack the requisite training and basic advising services that would keep them updated with new technological skills. Moreover, women are more likely to discontinue their businesses due to limited access to finance. Furthermore, women face restrictive legal and institutional burdens when establishing their business or when starting a new one. In addition, cultural constraints are another challenge that negatively influence women's credibility, their empowerment and self-confidence. The current study, intends to investigate the challenges that female entrepreneurs encounter, as business owners or start-up entrepreneurs in Egypt. The study contributes to the literature on women entrepreneurs by highlighting the challenges they face and presenting solutions that could help to promote their contribution in the economy. The results are based on semi-structured, face to face and phone interviews with seventeen female entrepreneurs from different business fields across different ages, ranging from 25 to 45 years old.